Modifying an approximation process using non-Newtonian calculus - AGRATINI, Octavian; KARSLI, Harun (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In the present note we modify a linear positive Markov process of discrete type by using so called multiplicative calculus. In this framework, a convergence property and the error of approximation are established. In the final part some numerical examples are delivered. Mathematics Subject Classification (2010): 41A36, 47S30.